EFFECTS OF PRENATAL GENTLE YOGA ON THE INCIDENCE AND SEVERITY OF PERINEAL RUPTURE IN VAGINAL DELIVERY: A QUASI-EXPERIMENTAL STUDY - Frida Sisternike Pay; Ummu Zakiah (JTH: Journal of Technology and Health, 2026)
Perineal rupture remains a common obstetric complication in vaginal delivery and contributes significantly to maternal morbidity. This study aimed to evaluate the effects of prenatal gentle yoga on the incidence and severity of perineal rupture among third-trimester pregnant women undergoing vaginal delivery. A quasi-experimental study with a control group design was conducted at Sikumana Community Health Center from February to March 2026 involving 30 participants, divided into an intervention group (n=15) and a control group (n=15). The intervention group received prenatal gentle yoga sessions three times per week for four weeks, while the control group received standard antenatal care. Data were collected using observation sheets and medical records, and analyzed using Chi-square test, Mann-Whitney U test, and logistic regression. The results showed that the incidence of perineal rupture was significantly lower in the intervention group (40%) compared to the control group (73.3%) (p=0.048). The severity of perineal rupture was also significantly reduced, with no cases of severe rupture in the intervention group and a significant difference between groups (p=0.021). Logistic regression analysis indicated that prenatal gentle yoga reduced the risk of perineal rupture by approximately 72% (OR=0.28; p=0.041). In conclusion, prenatal gentle yoga may serve as a promising non-pharmacological intervention to reduce the incidence and severity of perineal rupture among pregnant women undergoing vaginal delivery. However, considering the quasi-experimental design and relatively small sample size, further large-scale randomized studies are required to confirm these findings before broad clinical implementation.